Euthanasia as an option facing suffering? A look from Psychiatry - Hernández Santilllán, Gina (2020)
Euthanasia has been leading the debate about the end of life, lately. The "right to a dignified death" is proposed; however, "dying" does not constitute a right in itself and dignity is an attribute of all human life. For its part, Psychiatry has been concerned during the last century with preparing documents, such as, the Hawaii Declaration (1977) and the Madrid Declaration (1996) to ethically regulate the practice of the profession. Surprisingly, countries like the Netherlands and, recently, Spain approve euthanasia in their legislation, at the risk of falling into the “slippery slope” phenomenon and losing control. As a solution, palliative care seeks the dignified treatment of the person who is about to die.